Analysis Interpersonal Communication In Medtek Company - wicaksono, muhammad fajar bayu; wolor, Christian wiradendi; marsofiyati, (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2025)
Interpersonal communication is communication that is needed in work activities so that each member of the division can understand each other to minimize misunderstandings in doing work. With the existence of interpersonal communication in a division itself, it can build work and create a conducive and comfortable work environment for employees. The data for this research was obtained through observation, interview, and documentation methods. This research aims to find out the interpersonal communication that exists in PT Medtek Jakata and what obstacles occur and design strategies that can be done to prevent or minimize the interpersonal communication barriers faced. The population used as informants to fulfill the data needed by researchers was 4 samples. The analysis of this research is organized using a descriptive approach method to provide a comprehensive picture of this research. The results of this study are communication barriers that occur in one of the divisions. The obstacle that occurs is the lack of means to communicate to superiors. The advice given is that the agency still provides a communication system that can be used for divisions that have duties or responsibilities that are different from other divisions.